The Creative Side of the Reflective Planner. Updating the Schön’s Findings - Stufano Melone, Maria Rosaria; Rabino, Giovanni (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The self-reflection on their own work has always been present in all designers, including architects and planners. In the mid 80-90 Donald Schön has made more explicit this aspect, which until then had not found a systematic scientific treatment.  The results of Schön are the basis of practical planning of the 90s period. However, the Schön's analysis reveals a context of knowledge of mental functioning typical of the conceiving period. From the 90s until now numerous advances in knowledge of the mechanisms of rationality, reflection and creativity have been made, and in this context we are interested in the progress made in the field of creativity.  We try to integrate and update the Schön's reflection with the new available theories such as the CK theory to offer planners a more innovated range of tools in order to understand and make better use of their creativity and self-reflection about their own creativity.